Failure to rescue patients after emergency laparotomy for large bowel perforation: analysis of the National Emergency Laparotomy Audit (NELA). Issue 1 (20th February 2021) - Peacock, O; Yanni, F; Kuryba, A; Cromwell, D; Lockwood, S; Anderson, I; Vohra, R S; ,
Abstract: Background: Past studies have highlighted variation in in-hospital mortality rates among hospitals performing emergency laparotomy for large bowel perforation. The aim of this study was to investigate whether failure to rescue (FTR) contributes to this variability. Methods: Patients aged 18 years or over requiring surgery for large bowel perforation between 2013 and 2016 were extracted from the National Emergency Laparotomy Audit (NELA) database. Information on complications were identified using linked Hospital Episode Statistics data and in-hospital deaths from the Office for National Statistics. The FTR rate was defined as the proportion of patients dying in hospital with a recorded complication, and was examined in hospitals grouped as having low, medium or high overall postoperative mortality. Results: Overall, 6413 patients were included with 1029 (16.0 per cent) in-hospital deaths. Some 3533 patients (55.1 per cent) had at least one complication: 1023 surgical (16.0 per cent) and 3332 medical (52.0 per cent) complications. There were 22 in-hospital deaths following a surgical complication alone, 685 deaths following a medical complication alone, 150 deaths following both a surgical and medical complication, and 172 deaths with no recorded complication. The risk of in-hospital death was high among patients who suffered either type of complication (857 deaths in 3533 patients; FTR rate 24.3 per cent): 172 deaths followed a surgical complication (FTR-surgical rate 16.8 per cent) and 835 deaths followed a medical complication (FTR-medical rate of 25.1 per cent). After adjustment for patient characteristics and hospital factors, hospitals grouped as having low, medium or high overall postoperative mortality did not have different FTR rates ( P = 0.770). Conclusion: Among patients having emergency laparotomy for large bowel perforation, efforts to reduce the risk of in-hospital death should focus on reducing avoidable complications. There was no evidence of variation in FTR rates across National Health Service hospitals in England. Abstract : The aims of this study were to evaluate rates of complications, failure to rescue (FTR) and interprovider differences in patients undergoing emergency laparotomy for large bowel perforation in England. The FTR-surgical rate was 16.8 per cent and the FTR-medical rate was 25.1 per cent. FTR rates following emergency laparotomy for large bowel perforation are high, with no evidence of variation between hospitals.